Sartorius Muscle Flaps for Vascular Groin Wound Complications. Issue 11 (November 2015) - Brewer, Michael B.; Ochoa, Christian J.; Woo, Karen; Wartman, Sarah M.; Nikolian, Vahagn; Han, Sukgu; Weaver, Fred A.; Rowe, Vincent L.
Sartorius myoplasty (SM) has been used as an adjunct for soft tissue coverage in vascular groin wound complications. However, the reliability of SM as a primary muscle flap has been questioned. The purpose of this study is to determine the reliability of SM performed by vascular surgeons in the management of vascular groin wound complications. A retrospective review was performed on all patients who underwent SM from 1997 to 2012. The three indications for SM were prophylactic, infection, and noninfectious wound complication. Failure of SM was defined as operative reintervention for bleeding, persistent wound drainage, or infection. A total of 99 patients underwent 103 SM procedures. The patients were 43 per cent male and 57 per cent female; the mean age was 69 years. The indication for SM was infectious in 62 cases (60%), prophylactic in 21 cases (20%), and noninfectious in the remaining 20 cases. Failure of SM occurred in 11 cases (11%). Of these, salvage bypass and/or salvage muscle flap was required in eight cases (73%). When salvage bypass was required, extra-anatomic obturator bypass was performed in 80 per cent of cases. Salvage wound coverage included rectus abdominus flap (60%), rotational flap (20%), and skin grafting (20%). Seventy-three per cent of failures came from the infectious wound group. The most common reason for SM failure was hemorrhage (45%). In 82 per cent of the cases, the sartorius muscle was still viable at reoperation and was used for continued muscle coverage. SM performed by the vascular surgeon provides reliable soft tissue coverage for vascular groin wound complications and should be used as the primary muscle flap in the majority of patients. In cases of SM failure, the vascular surgeon should consider other more extensive muscle flap options.